The effect of self-efficacy and self-management training on efficacy and stress in diabetes mellitus patients - Gultom, Agustina Boru; Batubara, Arbani (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2022)
Background: Quality of life in patients with diabetes mellitus still tends to be low. This is caused by low self-efficacy and self-management and is followed by a condition that connects the two variables in the form of stress. Therefore, there is a need for efficacy and self-management training in patients with diabetes mellitus. Objective: The purpose of this study was to analyze the effect of self-efficacy and diabetes self-management training on diabetes mellitus patients. Methods: This is a quasi-experimental study with a design without a control group; as many as 34 people with diabetes were included in the study. Stress and efficacy levels were measured before and after being given diabetes self-management and efficacy training. The Wilcoxon test analyzed data.. Results: Before training, the average self-efficacy score was 44.21, while after training was 58.76, p<0.0001. The average stress score before training was 44.41; after training, it decreased to 30.29, p<0.0001. Conclusion: Â Diabetes self-efficacy and self-management training increases efficacy and reduces stress in diabetes mellitus patients.